The Influence of the Participatory Learning Approach (PLA) on Mothers' Knowledge and Awareness in Stunting Prevention: A Quasi-Experimental Study - Alamsyah Lukito; Zaim Anshari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Mothers play a crucial role in ensuring proper family nutrition to prevent stunting. Although various educational and counseling programs have been implemented to improve maternal knowledge, many remain conventional and one-directional, limiting active participation and impact. The Participatory Learning Approach (PLA) has been developed to promote engagement, deeper understanding, and awareness related to stunting prevention. Methods: This study examined the effect of the Participatory Learning Approach on maternal knowledge and awareness of stunting prevention using a quasi experimental design with intervention and control groups. Mothers participated in a community based stunting prevention program, in which the intervention group received participatory learning activities, while the control group received conventional education. Changes in knowledge and awareness were assessed before and after the intervention using appropriate statistical analyses. Unlike previous studies that employed prolonged participatory interventions, this study provides empirical evidence that a short, one day participatory learning program can effectively enhance maternal awareness of stunting prevention in a community based setting. Results: Most participants had high school education and were married. Knowledge scores increased significantly in the intervention group (12.59 ± 2.76 to 13.67 ± 3.22; p = 0.001) and in the control group (14.13 ± 2.65 to 15.43 ± 1.73; p = 0.002), with Independent t-tests indicated no statistically significant difference in knowledge gains between the intervention and control groups, although the participatory approach demonstrated meaningful improvements in maternal awareness. Maternal awareness of prenatal check-ups rose from 66.6% to 88.8%, and all participants acknowledged the importance of exclusive breastfeeding and dietary diversity after PLA. Conclusion: This study demonstrates that a short duration, community based Participatory Learning Approach (PLA) can effectively enhance maternal knowledge and, more importantly, maternal awareness related to stunting prevention. Although knowledge gains were comparable between participatory and conventional education, PLA showed added value in strengthening awareness of key preventive practices, including antenatal care, exclusive breastfeeding, and dietary diversity. These findings provide preliminary evidence that even a one day participatory learning intervention can serve as a feasible and contextually appropriate strategy for community based stunting prevention programs in resource-limited settings.